Urgensi Perubahan Undang-Undang Nomor 20 Tahun 2013 tentang Pendidikan Kedokteran - Kurnia Ningsih, Hilda; Herning Sitaboeana, Toendjoeng (Fakultas Hukum Universitas Mulawarman, 2023)
Law Number 20 of 2013 on Medical Education serves as the primary legal basis for the implementation of the medical education system in Indonesia. This article identifies several critical issues in the implementation of medical education, including high tuition fees, substandard quality of graduates, uneven distribution of doctors across Indonesia, ambiguity regarding professional organizations, and problems with the Competency Test for Medical Education Students (UKMPPD) considered unjust. This research utilizes a juridical-normative research method to elaborate on these issues by detailing applicable legislation. The findings emphasize the urgency of amending the Medical Education Law to ensure public access to quality doctors, equitable distribution across regions, and recommend abolishing the UKMPPD perceived as unjust for medical students. These changes are expected to create a more inclusive, efficient, and responsive medical education system to meet the needs of the Indonesian population. By adhering to these recommendations, it is hoped that the organization of medical education can produce graduates better prepared to face the challenges of the medical profession and provide quality healthcare services to the people of Indonesia